Spatially homogeneous string cosmological models with bulk viscosity in f(R, T) gravity theory - Ram S.; Priyanka (My University, 2025)
We discuss the field equations in f(R,T) gravity theory for the general class of Bianchi models filled with bulk viscous fluid together with a one-dimensional cosmic strings. We obtain two classes of cosmological solutions of the field equation by setting the average scale factor and one of the scale factors of the model proportional to a power function of the spatial volume. One class of solution represents on accelerated expanding universe having in the infinite past singularity. The other class of solution also represents on accelerated expanding having singularity at the initial time. The physical and kinematical properties of the models are discussed. We observe that the models of the two classes are compatible with the results of recent observations. © Electronic Journal of Theoretical Physics.